Clinical profile of diabetic foot ulcer patients in referral hospital Jambi: A-cross sectional study - Fitrianingsih, Fitrianingsih; Sania, Gina; Maimum, Maimum (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2025)
Background: Diabetic foot ulcer (DFU) is a chronic complication of diabetes mellitus (DM) and remains a significant challenge in morbidity, mortality, and disability among diabetic patients. This study aims to identify the sociodemographic and clinical characteristics of hospitalized DFU patients at Raden Mattaher General Hospital, Jambi. Method: This retrospective cross-sectional study was conducted at Raden Mattaher General Hospital, Jambi, Indonesia. A total of 31 patients data were collected from the medical records of DFU patients hospitalized at Raden Mattaher General Hospital in 2022. The variables observed were age, sex, residence, comorbidities, type of DM, random blood glucose levels (RBG), amputation rate, mortality, and length of stay (LOS). Results: The mean age of DFU patients was 55.6 ± 12.6 years, with females accounting for the majority (67.7%). Most patients lived outside Jambi City (74.2%), with more than one comorbidity (48.4%). All patients had type 2 diabetes mellitus (100.0%) with RBG level of 303.8 ± 205.8 mg/dL (mean±SD), amputation rate (19.4%), mortality rate (12.9%), and the mean LOS was 10.3 ± 6.9 days. Conclusion: This study indicates that most DFU patients have multiple comorbidities and poorly controlled blood glucose levels, which contribute to a higher risk of amputation, mortality, and prolonged hospitalization.